PROGNOSIS FACTORS AND TREATMENT TACTICS OF PATIENTS WITH UTERINE LEIOMYOSARCOMA - I. R. Gagua; V. V. Kuznetzov; N. I. Lazareva; V. M. Nechushkina; T. I. Zakharova; Zh. A. Zavolskaya (Опухоли женской репродуктивной системы, 2014)
Surgery is the main method of treatment of the patients with the uterine leiomyosarcoma. A standard extent of surgery is extirpation of the uterus without its appendages in the reproductive period or with uterine appendages in the postmenopause. The comparative analysis of the remote results of the treatment of the patients depending on the radicality of the performed surgery let to find out that the presence of the resid- ual tumor in the minor pelvis significantly worsens the course and the prognosis of the disease in the patients with the uterine leiomyosarco- ma. The adjuvant therapy is worth using for the prophylaxis of the distant metastasizing in the patients with the uterine leiomyosarcoma in the presence the poor prognosis factors. The postoperative radiotherapy of the patients is ineffective due to the low radio sensitivity of the tumor. The poor prognosis factors are: postmenopause, age over 60 years, the presence of the residual tumor, invasion depth more than half of the myometrium, invasion of the tumor up to the tunica serosa uteri, tumor size more than 5 cm, tumor necroses, low grade of the tumor differ- entiation, mitoses rate more than 10 in 10 view fields. The vital prognosis of the patients with the distant metastases depends on their charac- ter. In case of solitary metastases — the prognosis is favorable, in patients with the multiple metastases the prognosis worsens essentially.